2017
DOI: 10.1016/j.heares.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of model definitions and parameter values in finite element modeling of human middle ear mechanics

Abstract: The presented results provide insights into the importance of different features in middle ear finite element modeling. The application of three different individual middle ear geometries in a single study reduces the possibility that the conclusions are strongly affected by geometrical abnormalities. Some modeling variations that were hypothesized to be influential turned out to be of minor importance. Furthermore, it could be confirmed that different geometries, simulated using the same parameters and defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…It should be noted that our FE model is constructed only based on one human ear specimen. Based on a numerical study, Daniel et al [46] found that the human ear’s geometrical variation can lead to differences of 4 dB in the lower frequencies and up to 6 dB around 2 kHz, but similar shapes in the calculated response curves. Thus, the patients’ individual geometrical differences may alter our results quantitatively at lower frequencies and frequencies around 2 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that our FE model is constructed only based on one human ear specimen. Based on a numerical study, Daniel et al [46] found that the human ear’s geometrical variation can lead to differences of 4 dB in the lower frequencies and up to 6 dB around 2 kHz, but similar shapes in the calculated response curves. Thus, the patients’ individual geometrical differences may alter our results quantitatively at lower frequencies and frequencies around 2 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…The pars tensa of the tympanic membrane is modeled by using an orthotropic elastic description with different radial and circumferential elastic moduli. The radial Young's modulus decreases away from the umbo, as explained in [44]. All other components are modeled as isotropic materials.…”
Section: Assessment In a Finite-element Modelmentioning
confidence: 99%
“…Finite-element model employed to assess the performances of the middle ear prostheses. Panel A depicts the healthy middle ear according to[44] while Panel B shows the adaptation of the model to our study, where a 5-mm TORP replaces the native middle ear components between the eardrum and oval window. Legend: PS: pars tensa, PF: pars flaccida, M: malleus, I: incus, S: stapes, IMJ: incudomalleolar joint, ISJ: incudostapedial joint, TMC: tympano-mallear connection; AML: anterior mallear ligament, LML: lateral mallear ligament, PIL: posterior incudal ligament, SAL: stapedial annular ligament, SFP: stapes footplate, TTT: tensor tympani tendon, SMT, stapedial muscle tendon.…”
mentioning
confidence: 99%
“…All structures had the same Poisson's ratio and constant loss factor damping as a function of frequency, except for the columella having zero damping (e.g. De Greef et al, 2014bGreef et al, , 2017. The intracolumellar joint as defined in the current model requires a spring constant to describe its elastic properties instead of a Young's modulus and Poisson's ratio.…”
Section: Materials Propertiesmentioning
confidence: 99%